PENGEMBANGAN KEPEMIMPINAN SISWA MELALUI PELATIHAN PRAMUKA DI SMK NEGERI 1 AMANDRAYA - Derman Buulolo (Universitas Nias Raya, 2023)
The community service activity at SMK Negeri 1 Amandraya aims to develop students' leadership skills through scouting education. In the era of globalization, it is important for the younger generation to possess strong social and leadership skills. This activity involves training, outreach, and social activities that focus on the values of cooperation, discipline, and responsibility. Through the active participation of students and the community, this program successfully enhances social awareness and provides a positive impact on the surrounding environment. Evaluations show that students feel more confident and ready to contribute, while the community gains valuable new knowledge. This program not only strengthens the relationship between the school and the community but also creates a solid foundation for character development in future generations.